PERENCANAAN PEMBANGUNAN GEDUNG BARU BALAI NIKAH DAN MANASIK HAJI KUA KECAMATAN AUR BIRUGO TIGO BALEH KOTA BUKITTINGGI - Serly Supiana; Masril Masril; Yorizal Putra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
: The structure of this building uses reinforced concrete construction. The structure analysis goes through stages starting from Preliminary Design, structural loading, earthquake loading using the latest method, namely the response spectrum, analysis of the forces that occur in the structure using SAP2000 Version 20 by selecting the network system structure system (Grid System). The materials used are K-250 quality concrete (f'c = 20.75 MPa), screw reinforcement (fy = 400 MPa), plain reinforcement (fy = 240 MPa). For floor slab reinforcement, reinforcement is used for the x = 10-150 direction, while the y direction = 10-170. The column design uses steel quality fy = 400 MPa and concrete quality fc' = 20.75 MPa for columns 1 and 2 with a size of 35cm x 35cm. For the design of the beam using steel quality fy = 400 MPa and concrete quality fc' = 20.75 MPa with beam size 1 30cm x 50cm and beam 2 25cm x 45cm. And for stirrup reinforcement using steel quality fy = 240 MPa.Keywords: Preliminary Design, SAP2000 Analysis, Foundation, Loading ReinforcedConcrete, Reinforcement